2017
DOI: 10.2106/jbjs.cc.17.00003
|View full text |Cite
|
Sign up to set email alerts
|

Arthroscopic Osteochondral Autograft Transfer for Juvenile Osteochondritis Dissecans of the Humeral Head

Abstract: Arthroscopic osteochondral autograft transfer is an effective option for the treatment of OCD of the humeral head.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 15 publications
0
6
0
1
Order By: Relevance
“…Characteristics of the 14 studies meeting all inclusion criteria can be found in Table 1 . 1-6,17-24 There were 6 retrospective case series, 7 case reports, and 1 prospective case series. This resulted in a total of 100 shoulders in 98 patients.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Characteristics of the 14 studies meeting all inclusion criteria can be found in Table 1 . 1-6,17-24 There were 6 retrospective case series, 7 case reports, and 1 prospective case series. This resulted in a total of 100 shoulders in 98 patients.…”
Section: Resultsmentioning
confidence: 99%
“…1 The other 13 studies reported no complications in the perioperative period. 2-6,17-24 The overall rate of failure and/or reoperation ranged from 0% to 35% and 0% to 30%, respectively 6,17,20,23,24 ( Table 3 ). Of note, patients who required reoperation and patients who would choose not to undergo the initial procedure again were considered failures.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…A recent literature search resulted in 19 case reports describing OCD of the humeral head. For the review of these case reports, we decided to use only the available English reports, which resulted in 13 remaining articles (3)(4)(5)(7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18)(19)(20).…”
Section: Discussionmentioning
confidence: 99%
“…O joelho é a articulação mais acometida pela osteocondrite dissecante (5) , mas outras articulações podem ser acometidas (5)(6)(7)(8) . A osteocondrite dissecante pode apresentar-se na forma juvenil, quando há presença de fise aberta, ou adulta, quando já existe maturidade esquelética.…”
Section: Discussionunclassified